GE_GERICHTE P/16425/2015 vom 30. August 2018 - GE Cour de justice (2018)
CONTRAINTE(DROIT PÉNAL) ; PERSÉCUTION ; INJURE ; FIXATION DE LA PEINE ; CONCOURS D'INFRACTIONS ; PEINE PÉCUNIAIRE ; DÉFENSE D'OFFICE | CP.181; CP.22; CP.177.al1; CP.47; CP.49.al1; aCP.34; CPP.135